Catalyst for fuel cell, method for preparing the catalyst and membrane-electrode assembly containing the catalyst
By doping and/or partially alloying the PtCo alloy particles with transition metals, the problem of degradation of the durability of fuel cell catalysts is solved, and a significant improvement in catalyst performance and durability is achieved, and the cost is relatively low.
Patent Information
- Application Number
- CN202080061160.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-31
- Filing Date
- 2020-12-23
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2040-12-23
AI Technical Summary
The existing fuel cell catalysts have reduced durability due to Co dissolution of active sites during the fuel cell reaction of PtCo catalysts, and it is difficult to prepare catalysts with excellent performance and durability at low cost.
Catalysts with improved performance and durability were prepared by doping and/or partially alloying the PtCo alloy particles with a transition metal selected from V, Cr, Mn, Fe, Ni, Cu, W and Mo. The method includes preparing a first catalyst, mixing with the transition metal precursor, and performing heat treatment to complete doping and/or partial alloying.
The performance and durability of the catalyst are significantly improved, and the membrane-electrode assembly and fuel cells prepared using the catalysts of the present disclosure exhibit excellent performance and durability.
Smart Images

Figure CN114342129B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a catalyst for a fuel cell, a method for preparing the catalyst, and a membrane-electrode assembly comprising the catalyst. More specifically, the present invention relates to a catalyst for a fuel cell with improved performance and durability, a method for preparing the catalyst, and a membrane-electrode assembly comprising the catalyst. Background Art
[0002] Polymer electrolyte membrane fuel cells (PEMFCs) generate electricity using a stacked structure of unit cells, each of which includes a membrane-electrode assembly (MEA) and a separator (also called a "bipolar plate"), and have attracted attention as a next-generation energy source that can replace fossil fuels due to their high energy efficiency and environmental friendliness.
[0003] A membrane-electrode assembly generally includes an anode (also called "fuel electrode"), a cathode (also called "air electrode"), and a polymer electrolyte membrane located therebetween.
[0004] When a fuel such as hydrogen is supplied to the anode, the hydrogen at the anode is oxidized to generate protons (H + ) and electron (e - ). The generated protons are transferred to the cathode through the polymer electrolyte membrane, and the generated electrons are transferred to the cathode through an external circuit. The oxygen supplied to the cathode is combined with the protons and electrons, thereby being reduced to generate water.
[0005] Platinum or other noble metals having high catalytic activity and high corrosion resistance are used as metal catalysts for forming electrodes in a membrane-electrode assembly (MEA).
[0006] In order to increase the active surface area of the catalyst, a catalyst formed by dispersing metal catalyst particles on the surface of a conductive support (eg, carbon, metal oxide, or C 3 N 4 ) has been developed.
[0007] In order to promote the commercialization of fuel cells, the catalytic activity of metal catalysts must be further improved while reducing the amount of expensive platinum / precious metals used for this purpose. To this end, various types of alloys containing precious metals such as platinum have been proposed. For example, it is known that PtCo alloys have a higher catalytic activity than platinum despite the use of reduced amounts of platinum. In addition, in order to further improve PtCo alloys, research on ternary alloys obtained by alloying Pt and Co with a third transition metal is being actively carried out.
[0008] However, in recent years, it has been reported that during the fuel cell reaction of the PtCo catalyst, the durability is reduced due to the dissolution of Co from the active site. Therefore, there is a need to improve the durability.
[0009] Furthermore, metal or alloy catalysts that can be prepared at relatively low cost and have satisfactory performance and durability have not yet been developed. Summary of the invention
[0010] Technical issues
[0011] Accordingly, the present disclosure is directed to a catalyst for a fuel cell, a method of preparing the catalyst, and a membrane-electrode assembly including the catalyst, which are capable of preventing the problems caused by the above-mentioned limitations and disadvantages of the related art.
[0012] An object of the present disclosure is to provide a catalyst for a fuel cell having excellent performance and durability.
[0013] Another object of the present disclosure is to provide a method of preparing a catalyst for a fuel cell having excellent performance and durability.
[0014] Another object of the present disclosure is to provide a membrane-electrode assembly having excellent performance and durability.
[0015] In addition to the aspects of the present disclosure described above, other features and advantages of the present disclosure will be described in the following detailed description or will be more clearly understood by those skilled in the art to which the present disclosure belongs.
[0016] Technical Solution
[0017] According to one aspect of the present disclosure, there is provided a catalyst for a fuel cell, comprising: a carrier; and PtCo alloy particles supported on the carrier, wherein the PtCo alloy particles include a transition metal-doped or transition metal partially alloyed surface modified by at least one transition metal selected from V, Cr, Mn, Fe, Ni, Cu, W and Mo, or a transition metal-doped or transition metal partially alloyed internal region containing the transition metal.
[0018] The PtCo alloy particles may also include a transition metal-free surface or a transition metal-free interior region in which no transition metal is present.
[0019] The PtCo alloy particle may include a transition metal-doped or transition metal partially alloyed interior region and a transition metal-free interior region, and the transition metal-free interior region may be farther from an exposed surface of the PtCo alloy particle than the transition metal-doped or transition metal partially alloyed interior region.
[0020] In the PtCo alloy particles, a molar ratio of Co to Pt may be 0.05 to 0.4, and a molar ratio of the transition metal to Pt may be 0.03 to 0.15.
[0021] The transition metal may be Cu.
[0022] In another aspect of the present disclosure, a method for preparing a catalyst for a fuel cell is provided, the method comprising: preparing a first catalyst comprising a carrier and PtCo alloy particles loaded on the carrier; mixing the first catalyst with a precursor of at least one transition metal selected from V, Cr, Mn, Fe, Ni, Cu, W and Mo to obtain a mixture; and heat treating the mixture.
[0023] The molar ratio of Co to Pt in the PtCo alloy particles of the first catalyst may be 0.05 to 0.4.
[0024] The transition metal may be Cu, and the precursor may be CuCl2, CuSO4, CuO, Cu(CO2CH3)2, CuS, Cu(NO3)2, Cu(ClO4)2, CuCO3, or a mixture of two or more thereof.
[0025] The mixture can be obtained by: (i) dispersing the first catalyst in a solution or dispersion containing the precursor; (ii) mixing a solution or dispersion containing the precursor with a dispersion containing the first catalyst; or (iii) directly mixing the solid precursor with the solid first catalyst.
[0026] The mixture can be obtained by: (i) dispersing the first catalyst in a solution or dispersion containing the precursor; or (ii) mixing a solution or dispersion containing the precursor with a dispersion containing the first catalyst. In addition, the method for preparing the catalyst can also include drying the mixture before the heat treatment.
[0027] The heat treatment may be performed at 100° C. to 300° C. for 10 to 60 minutes in an atmosphere of a reducing gas or in an atmosphere of a mixed gas including a reducing gas and an inert gas.
[0028] The heat treatment may be performed in an atmosphere of a reducing gas, and the reducing gas may be NH 3 gas.
[0029] The heat treatment may be performed in an atmosphere of a mixed gas, and the mixed gas may contain 5 volume % to 15 volume % of a reducing gas.
[0030] The heat treatment may be performed in an atmosphere of a mixed gas, and the mixed gas may contain H 2 gas as a reducing gas and N 2 gas or Ar gas as an inert gas.
[0031] The heat treatment may be performed in an atmosphere of a mixed gas, and the mixed gas may contain NH 3 gas as a reducing gas and N 2 gas or Ar gas as an inert gas.
[0032] In another aspect of the present disclosure, a membrane-electrode assembly is provided, comprising: an anode; a cathode; and a polymer electrolyte membrane located between the anode and the cathode, wherein at least one of the anode and the cathode contains the above-mentioned catalyst.
[0033] The general description of the present disclosure provided above is only for illustration or description of the present disclosure and does not limit the scope of the present disclosure.
[0034] Beneficial Effects
[0035] According to the present disclosure, by doping and / or partially alloying the PtCo catalyst, specifically the PtCo alloy particles, with transition metals, both the performance and durability of the catalyst can be significantly improved. As a result, the membrane-electrode assembly prepared using the catalyst of the present disclosure and the fuel cell containing the catalyst can exhibit excellent performance and durability. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The accompanying drawings are provided for a better understanding of the present disclosure and constitute a part of the present specification, and are given for illustrating embodiments of the present disclosure and describing the principles and features of the present disclosure with reference to the following detailed description, wherein:
[0037] Figure 1 Schematically illustrates a catalyst of the present disclosure prepared by doping or partially alloying a PtCo catalyst with a transition metal;
[0038] Figure 2 (a) and (b) are transmission electron microscopy (TEM) and high-resolution transmission electron microscopy (HR-TEM) images of the catalyst of Example 1;
[0039] Figure 3 (a) and (b) are transmission electron microscopy (TEM) and high-resolution transmission electron microscopy (HR-TEM) images of the catalyst of Example 2;
[0040] Figure 4 is a transmission electron microscope (TEM) image showing the catalyst of Comparative Example 1;
[0041] Figure 5 is a transmission electron microscope (TEM) image showing the catalyst of Comparative Example 2;
[0042] Figure 6 is a diagram showing the XRD analysis results of the catalysts of Examples and Comparative Examples;
[0043] Figure 7 are graphs showing the results of cyclic voltammetry (CV) tests of electrodes formed using the catalysts of Examples and Comparative Examples, respectively;
[0044] Figure 8 : is a graph showing the results of LSV (Linear Sweep Voltammetry) tests of electrodes formed of catalysts of Examples and Comparative Examples, respectively;
[0045] Fig. 9 are graphs showing the performance of membrane-electrode assemblies prepared using the catalysts of Examples and Comparative Examples, respectively, under high humidity operating conditions (100% RH / 100% RH); and
[0046] Fig.10 : is a graph showing the performance of membrane-electrode assemblies prepared using the catalysts of Examples and Comparative Examples, respectively, under low humidity operating conditions (50% RH / 50% RH). DETAILED DESCRIPTION
[0047] Hereinafter, the present disclosure will be described in more detail with reference to specific examples. However, the following examples are provided only for a better understanding of the present disclosure and should not be construed as limiting the scope of the present disclosure.
[0048] Figure 1 The catalyst 100 of the present disclosure is schematically shown, which is prepared by doping and / or partially alloying a conventional PtCo catalyst (hereinafter referred to as "first catalyst") 10 with a transition metal.
[0049] like Figure 1 As shown in FIG. 1 , the first catalyst 10 is a commercially available catalyst or a pre-prepared catalyst, which includes a carrier 11 and PtCo alloy particles 12 supported on the carrier 11 .
[0050] The support 11 may be (i) a carbon-based support; (ii) a porous inorganic oxide support such as zirconia, alumina, titania, silica, and ceria; or (iii) a zeolite support.
[0051] When the carrier 11 is a carbon-based carrier, the first catalyst 10 can be represented as a PtCo / C catalyst. The carbon-based carrier can be graphite, super P, carbon fiber, carbon sheet, carbon black, Ketjen black, superconductive acetylene black (Denka black), acetylene black (acetylene black), carbon nanotube (CNT), carbon sphere, carbon ribbon, fullerene, activated carbon, carbon nanowire, carbon nanosphere, carbon nanohorn, carbon nanocage, carbon nanoring, ordered nano / mesoporous carbon, carbon aerogel, mesoporous carbon, graphene, stable carbon, or a combination of two or more thereof.
[0052] like Figure 1As shown, the PtCo alloy particle 12 is a particle formed of a binary alloy of Pt and Co, and thus Pt and Co are uniformly distributed in the particle. According to one embodiment of the present disclosure, the molar ratio of Co to Pt in the PtCo alloy particle 12 may be 0.05 to 0.4.
[0053] According to the present disclosure, the first catalyst 10 is doped and / or partially alloyed with at least one transition metal selected from V, Cr, Mn, Fe, Ni, Cu, W, and Mo.
[0054] The doping and / or partial alloying process includes mixing a precursor of a transition metal with the first catalyst 10 to obtain a mixture and heat-treating the mixture.
[0055] For example, the transition metal may be Cu, and the precursor of the transition metal may be CuCl2, CuSO4, CuO, Cu(CO2CH3)2, CuS, Cu(NO3)2, Cu(ClO4)2, CuCO3, or a mixture of two or more thereof.
[0056] The mixture can be obtained by: (i) a first method: dispersing the first catalyst in a solution or dispersion containing the precursor; (ii) a second method: mixing a solution or dispersion containing the precursor with a dispersion containing the first catalyst; or (iii) a third method: directly mixing the solid phase of the precursor with the solid phase of the first catalyst.
[0057] However, the liquid mixture obtained by the first method or the second method may be more uniform than the solid mixture obtained by the third method, and thus is more conducive to uniformly doping and / or partially alloying the first catalyst.
[0058] When the mixture is obtained by the first method or the second method, the method may further include drying the mixture before the heat treatment.
[0059] The heat treatment of the mixture may be performed in an atmosphere of a reducing gas or in an atmosphere of a mixed gas including an inert gas and a reducing gas at 100 to 300° C. for 10 to 60 minutes. For example, the heat treatment of the mixture may be performed in a tube furnace.
[0060] When the mixture is heat-treated in an atmosphere of a reducing gas, the reducing gas may be NH 3 gas.
[0061] When the mixture is heat-treated in an atmosphere of a mixed gas containing an inert gas and a reducing gas, the inert gas may be N2 gas or Ar gas, and the reducing gas may be H2 gas, NH3 gas, or a combination thereof. The mixed gas may contain 5 volume % to 15 volume % of the reducing gas and 85 volume % to 95 volume % of the inert gas.
[0062] The heat treatment performed in a mixed gas atmosphere can be performed by introducing the mixture into an electric furnace, raising the temperature under an inert gas (e.g., N2 gas or Ar gas), and supplying a reducing gas (e.g., NH3 gas) into the electric furnace when the temperature of the electric furnace reaches a target temperature.
[0063] The catalyst 100 of the present disclosure may be obtained by completing doping and / or partial alloying of the PtCo catalyst 10 with a transition metal through heat treatment of the mixture.
[0064] like Figure 1 As shown, the catalyst 100 for a fuel cell of the present disclosure includes a carrier 110 and PtCo alloy particles 120 supported on the carrier 110, wherein the PtCo alloy particles 120 are doped and / or partially alloyed with at least one transition metal selected from V, Cr, Mn, Fe, Ni, Cu, W and Mo.
[0065] The carrier 110 is the same as the carrier 11 of the first catalyst 10 used to prepare the catalyst 100. The carrier 110 may be (i) a carbon-based carrier; (ii) a porous inorganic oxide carrier such as zirconium oxide, aluminum oxide, titanium dioxide, silicon dioxide, and ceria; or (iii) a zeolite carrier. The carbon-based carrier may be graphite, super P, carbon fiber, carbon sheet, carbon black, Ketjen black, superconductive acetylene black, acetylene black, carbon nanotube (CNT), carbon sphere, carbon ribbon, fullerene, activated carbon, carbon nanowire, carbon nanosphere, carbon nanohorn, carbon nanocage, carbon nanoring, ordered nano / mesoporous carbon, carbon aerogel, mesoporous carbon, graphene, stabilized carbon, or a combination of two or more thereof.
[0066] like Figure 1 As shown in , the PtCo alloy particle 120 may include: (i) a transition metal-doped or transition metal partially alloyed surface modified by a transition metal; (ii) a transition metal-doped or transition metal partially alloyed internal region containing a transition metal; or (iii) both a transition metal-doped or transition metal partially alloyed surface and a transition metal-doped or transition metal partially alloyed internal region.
[0067] Since the PtCo alloy particles 120 of the present disclosure are substantially binary alloys of Pt and Co, the PtCo alloy particles 120 also include a transition metal-free surface and / or a transition metal-free internal region in which no transition metal is present. The transition metal-doped or transition metal partially alloyed surface and the transition metal-doped or transition metal partially alloyed internal region contain a mixture of Pt, Co, and Cu, while the transition metal-free surface and the transition metal-free internal region contain Pt and Co, but do not contain Cu.
[0068] The PtCo alloy particle 120 of the present disclosure is different from the ternary alloy particle in that it is basically a binary alloy particle of Pt and Co that is only partially doped and / or partially alloyed with a transition metal (i.e., a particle including a surface free of transition metal and / or an internal region free of transition metal), while the particle of the ternary alloy is a particle obtained by alloying a transition metal with Pt and Co (i.e., a particle in which the transition metal is uniformly distributed throughout the particle together with Pt and Co).
[0069] like Figure 1 As shown, the PtCo alloy particle 120 may have: (i) a first structure including: a transition metal-doped or partially alloyed surface, and an internal region without transition metal (corresponding to the entire internal region of the particle); (ii) a second structure including: a transition metal-free surface, a transition metal-doped or partially alloyed internal region, and an internal region without transition metal; or (iii) a third structure including: a transition metal-doped or partially alloyed surface, a transition metal-doped or partially alloyed internal region, and an internal region without transition metal. The first structure and the third structure may also include a transition metal-free surface, respectively.
[0070] When the PtCo alloy particle 120 has the second structure or the third structure, the transition metal-free inner region may be farther from the exposed surface of the PtCo alloy particle than the transition metal-doped or transition metal partially alloyed inner region.
[0071] According to one embodiment of the present disclosure, a molar ratio of Co to Pt in the PtCo alloy particles 120 may be 0.05 to 0.4, and a molar ratio of transition metal to Pt may be 0.03 to 0.15.
[0072] The catalyst 100 for a fuel cell of the present disclosure prepared by doping and / or partially alloying the PtCo alloy particles 12 of the PtCo catalyst 10 with a transition metal (Me) is denoted as a Me-PtCo catalyst, which is different from a PtCoMe catalyst which is a ternary alloy of Pt, Co and a transition metal (Me).
[0073] For example, the catalyst 100 of the present disclosure may be a Cu-PtCo catalyst including PtCo alloy particles 120 doped and / or partially alloyed with Cu, which is different from a PtCoCu catalyst including particles formed of a ternary alloy of Pt, Co, and Cu.
[0074] In addition, when the support 110 is a carbon-based support and the transition metal doped and / or partially alloyed in the PtCo alloy particles 120 is Cu, the catalyst 100 of the present disclosure is represented as a Cu-PtCo / C catalyst, which is different from the PtCoCu / C catalyst in which a ternary alloy of Pt, Co and Cu is dispersed in the form of particles on a carbon-based support.
[0075] The catalyst 100 of the present disclosure is dispersed in a dispersion medium together with an ionomer to obtain an electrode slurry, and the electrode slurry is used to form an anode and a cathode on both surfaces of a polymer electrolyte membrane (PEM) by decal transfer or direct coating to prepare a membrane-electrode assembly (MEA) of the present disclosure.
[0076] Alternatively, the membrane-electrode assembly (MEA) of the present disclosure includes an anode, a cathode, and a polymer electrolyte membrane (PEM) located therebetween, wherein one of the anode and the cathode contains the catalyst 100 of the present disclosure, and the other contains a conventional platinum or platinum alloy catalyst (e.g., Pt / C catalyst, PtCo / C catalyst, PtCoCu / C catalyst, PtCoNi / C catalyst, etc.) instead of the catalyst 100 of the present disclosure.
[0077] The ionomer dispersed in the dispersion medium together with the catalyst 100 serves to transfer cations, and also functions as a binder for improving adhesion between the catalyst 100 and the polymer electrolyte membrane (PEM).
[0078] The ionomer may have at least one ion-conducting group selected from the group consisting of a sulfonic acid group, a carboxyl group, a boric acid group, a phosphoric acid group, an imide group, a sulfonimide group, a sulfonamide group, and a fluorinated sulfonic acid group.
[0079] For example, the ionomer may be a fluorine-based ionomer such as poly(perfluorosulfonic acid) or poly(perfluorocarboxylic acid).
[0080] Alternatively, the ionomer can be a hydrocarbon polymer such as a sulfonated polyimide (S-PI), a sulfonated polyarylethersulfone (S-PAES), a sulfonated polyetheretherketone (SPEEK), a sulfonated polybenzimidazole (SPBI), a sulfonated polysulfone (S-PSU), a sulfonated polystyrene (S-PS), a sulfonated polyphosphazene, a sulfonated polyquinoxaline, a sulfonated polyketone, a sulfonated polyphenylene ether, a sulfonated polyethersulfone, a sulfonated polyetherketone, a sulfonated polyphenylene sulfide, a sulfonated polyphenylene sulfide sulfone, a sulfonated polyphenylene sulfide sulfone nitrile, a sulfonated polyarylether, a sulfonated polyarylether nitrile, a sulfonated polyarylether ether nitrile, or a sulfonated polyarylether sulfoneketone.
[0081] The dispersion medium of the electrode slurry in which the catalyst 100 and the electrode slurry are dispersed may be water, a hydrophilic solvent, an organic solvent, or a mixture of two or more thereof.
[0082] The hydrophilic solvent may be a compound containing a linear or branched saturated or unsaturated hydrocarbon having 1 to 12 carbon atoms as a main chain and having at least one functional group selected from alcohol, isopropanol, ketone, aldehyde, carbonate, carboxylate, carboxylic acid, ether and amide.
[0083] The organic solvent may be N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO), tetrahydrofuran (THF), dimethylacetamide (DMAc), or a mixture of two or more thereof, but is not limited thereto.
[0084] Hereinafter, the present disclosure will be described in more detail with reference to specific examples. These examples are provided only for better understanding and should not be construed as limiting the scope of the present disclosure.
[0085] Example 1
[0086] 1g PtCo / C catalyst (that is, the first catalyst) is dispersed in water to obtain a dispersion. In addition, 1.3gCuCl2 is dissolved in water to obtain a Cu precursor solution. The dispersion is uniformly mixed with the Cu precursor solution to obtain a mixed solution, and the mixed solution is dried to remove moisture to obtain a solid as a mixture of the PtCo / C catalyst and the Cu precursor. The solid is introduced into a tubular furnace, and in a mixed gas atmosphere of H2 and N2, heat-treated at 250°C for 30 minutes to obtain a Cu-PtCo / C catalyst (hereinafter referred to as Cu-PtCo / C_H2 catalyst).
[0087] Example 2
[0088] A Cu—PtCo / C catalyst (hereinafter, the catalyst is referred to as Cu—PtCo / C_NH 3 catalyst) was obtained in the same manner as in Example 1 except that the heat treatment was carried out in an NH 3 gas atmosphere.
[0089] Comparative Example 1
[0090] The same type of PtCo / C catalyst as that used as the first catalyst in Example 1 was prepared.
[0091] Comparative Example 2
[0092] The support is dispersed in water to obtain a dispersion. Subsequently, a Pt precursor (H2PtCl6), a Co precursor (CoCl2) and a Cu precursor (CuCl2) are mixed with the dispersion, and then a reduction reaction is carried out by a polyol reduction method to obtain a PtCoCu / C catalyst as a ternary alloy catalyst.
[0093] [Transmission electron microscopy (TEM) analysis of catalyst]
[0094] Figure 2 (a) and (b) are transmission electron microscope (TEM) images and high-resolution transmission electron microscope (HR-TEM) images of the Cu-PtCo / C_H2 catalyst of Example 1, Figure 3 (a) and (b) are TEM and HR-TEM images of the Cu-PtCo / C_NH3 catalyst of Example 2, Figure 4 is a TEM image showing the PtCo / C catalyst of Comparative Example 1, Figure 5 : is a TEM image showing the PtCoCu / C catalyst of Comparative Example 2.
[0095] from Figures 2 to 5 It can be seen that there is no significant difference in particle distribution and state between the catalyst of the example and the catalyst of the comparative example, except that the particle size is slightly increased.
[0096] From the HR-TEM image of Cu-PtCo / C_H2 catalyst [ Figure 2 (b)] and HR-TEM images of Cu-PtCo / C_NH3 catalysts[ Figure 3 (b)] It can be seen that the Cu-PtCo / C_H2 catalyst of Example 1 does not have any significant difference from the Cu-PtCo / C_NH3 catalyst of Example 2, except that the particle size is slightly larger than that of the Cu-PtCo / C_NH3 catalyst of Example 2. That is, it can be seen that there is no big difference depending on the type of reducing gas supplied during the heat treatment.
[0097] [XRD analysis of catalyst]
[0098] Figure 6 is a graph showing the XRD analysis results of the catalysts of the embodiments and comparative examples. Figure 6 It can be seen that there is no significant difference between the catalyst of the example and the catalyst of the comparative example, except that the particle size is slightly increased.
[0099] [CV test, LSV test and voltage cycle test]
[0100] The catalyst was dispersed in a mixture of isopropanol and water in a volume ratio of 7:3 by ultrasonic dispersion to prepare an electrode slurry. The electrode slurry was cast on a rotating disk electrode (RDE) and dried to prepare an electrode. The electrode was subjected to a cyclic voltammetry (CV) test using an electrochemical measuring device (temperature: room temperature, electrolyte: 0.1 M HClO4 aqueous solution saturated with N2) to measure the electrochemical surface area (ECSA) of the catalyst.
[0101] Figure 7 1 is a graph showing the results of cyclic voltammetry (CV) tests of electrodes prepared from catalysts of Examples and Comparative Examples, respectively. The catalysts of Examples, particularly the Cu-PtCo / C_H2 catalyst of Example 1, exhibit an increased electrochemical surface area (ECSA).
[0102] Subsequently, the electrolyte was saturated with O2 and then subjected to LSV (linear sweep voltammetry) test to evaluate the redox reaction (ORR) activity of the catalyst.
[0103] Figure 8 1 is a graph showing the linear sweep voltammetry (LSV) test results of electrodes prepared from catalysts of Examples and Comparative Examples. The catalysts of Examples, especially the Cu-PtCo / C_H2 catalyst of Example 1, exhibited better ORR activity.
[0104] In addition, in order to evaluate the electrochemical durability of the catalyst, a voltage cycle test (30,000 cycles) was performed on an electrolyte saturated with O2 at 0.6 V to 1.0 V. The electrochemical surface area (ECSA) was measured before and after the voltage cycle test, and the ECSA loss was calculated based on the measured values, and the results are shown in Table 1 below.
[0105] [Table 1]
[0106] Example 1 Example 2 Comparative Example 1 Comparative Example 2 catalyst <![CDATA[Cu-PtCo / C_H2]]> <![CDATA[Cu-PtCo / C_NH3]]> PtCo / C PtCoCu / C ECSA Losses 28% 30% 36% 35%
[0107] As can be seen from Table 1 above, the catalysts of the embodiments, especially the Cu-PtCo / C_H2 catalyst of Example 1, show significantly lower ECSA loss than the catalysts of the comparative examples, which indicates that the Cu-PtCo / C catalyst of the present disclosure prepared by doping and / or partially alloying the PtCo alloy particles with Cu has higher durability than the PtCo / C catalyst of Comparative Example 1 and the PtCoCu / C catalyst of Comparative Example 2.
[0108] [MEA performance test]
[0109] The catalyst was dispersed in a mixture of isopropanol and water in a volume ratio of 7:3 by ultrasonic dispersion to prepare an electrode slurry. The electrode slurry was placed at 25 cm 2 The area is coated on the first release film and the second release film, respectively, and dried in an oven at 90°C for 8 hours to form a square anode and cathode, respectively. Subsequently, the first release film, the polymer electrolyte membrane and the second release film are laminated and hot pressed so that the anode and the cathode are in contact with the first surface and the second surface of the polymer electrolyte membrane prepared using perfluorosulfonic acid, respectively. Then, the first release film and the second release film are removed to complete the membrane-electrode assembly. The membrane-electrode assembly is connected to a fuel cell unit battery test device, and after activation, the output performance is measured at 65°C and normal pressure under high humidity operating conditions (100%RH / 100%RH) and low humidity operating conditions (50%RH / 50%RH).
[0110] Fig. 9 and Fig.10 : are graphs showing the performance of membrane-electrode assemblies prepared using the catalysts of Examples and Comparative Examples, respectively, under high humidity and low humidity operating conditions. Fig. 9 and Fig.10 It is shown that the membrane-electrode assembly prepared with the Cu-PtCo / C catalyst of the embodiment exhibits improved performance under both high humidity operating conditions and low humidity operating conditions compared with the membrane-electrode assemblies prepared with the PtCo / C and PtCoCu / C catalysts of the comparative examples.
Claims
1. A catalyst for a fuel cell, comprising: Carrier; and PtCo alloy particles supported on the carrier, wherein the PtCo alloy particles include (i) an internal region doped with a transition metal or partially alloyed with a transition metal, wherein the transition metal includes at least one selected from V, Cr, Mn, Fe, Ni, Cu, W and Mo, (ii) an internal region free of transition metal, wherein the transition metal is not present, and (iii) a surface free of transition metal, wherein the transition metal is not present, and The transition metal-free inner region is farther from the exposed surface of the PtCo alloy particle than the transition metal-doped or transition metal partially alloyed inner region.
2. The catalyst for a fuel cell according to claim 1, wherein In the PtCo alloy particles, a molar ratio of Co to Pt is 0.05 to 0.4, and a molar ratio of the transition metal to Pt is 0.03 to 0.
15.
3. The catalyst for a fuel cell according to claim 1, wherein The transition metal is Cu.
4. A method for preparing a catalyst for a fuel cell, the method comprising: preparing a first catalyst including a carrier and PtCo alloy particles supported on the carrier; mixing the first catalyst with a precursor of at least one transition metal selected from V, Cr, Mn, Fe, Ni, Cu, W and Mo to obtain a mixture; and The mixture is heat treated at 100 to 300° C. for 10 to 60 minutes in an atmosphere of a reducing gas or a mixed gas atmosphere including a reducing gas and an inert gas, so that the PtCo alloy particles include (i) an internal region doped with a transition metal or partially alloyed with a transition metal containing the transition metal, (ii) an internal region not containing a transition metal, in which the transition metal is not present, and (iii) a surface not containing a transition metal, in which the transition metal is not present, The transition metal-free inner region is farther from the exposed surface of the PtCo alloy particle than the transition metal-doped or transition metal partially alloyed inner region.
5. The method according to claim 4, wherein: The molar ratio of Co to Pt in the PtCo alloy particles of the first catalyst is 0.05 to 0.
4.
6. The method according to claim 4, wherein: The transition metal is Cu, and The precursor is CuCl2, CuSO4, CuO, Cu(CO2CH3)2, CuS, Cu(NO3)2, Cu(ClO4)2, CuCO3, or a mixture of two or more thereof.
7. The method according to claim 4, wherein: The mixture is obtained by: (i) dispersing the first catalyst in a solution or dispersion containing the precursor; (ii) mixing the solution or dispersion containing the precursor with the dispersion containing the first catalyst; or (iii) directly mixing the solid-phase precursor with the solid-phase first catalyst.
8. The method according to claim 4, wherein: The mixture is obtained by: (i) dispersing the first catalyst in a solution or dispersion containing the precursor; or (ii) mixing a solution or dispersion containing the precursor with a dispersion containing the first catalyst, and The method further comprises drying the mixture prior to the heat treating.
9. The method according to claim 4, wherein: The heat treatment is performed in the reducing gas atmosphere, and The reducing gas is NH3 gas.
10. The method according to claim 4, wherein: The heat treatment is performed in the atmosphere of the mixed gas, and The mixed gas contains 5 volume % to 15 volume % of the reducing gas.
11. The method according to claim 4, wherein: The heat treatment is performed in the atmosphere of the mixed gas, and The mixed gas includes H 2 gas as a reducing gas and N 2 gas or Ar gas as an inert gas.
12. The method according to claim 4, wherein: The heat treatment is performed in the atmosphere of the mixed gas, and The mixed gas includes NH 3 gas as a reducing gas and N 2 gas or Ar gas as an inert gas.
13. A membrane-electrode assembly comprising: anode; cathode; and a polymer electrolyte membrane located between the anode and the cathode, Wherein, at least one of the anode and the cathode comprises the catalyst according to any one of claims 1 to 3.
Citation Information
Patent Citations
Method for manufacturing cathode catalyst layer for fuel battery
JP2016035869A
Platinum alloy powder and method for producing the same
JP2016148078A